Re-purposing Wind Turbine Blades: Matching strategies and Innovation Governance Forms - Andersen, Poul Houman; Ali, Majid; Anvari-Moghaddam, Amjad; P. Nielsen, Rudi; Enggrob Simonsen, Morten (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The decommissioning of wind turbine blades poses an escalating environmental and waste management challenge, as the composite materials found in these blades are difficult to recycle and often end up in landfills. With the projected growth in retired wind turbine blades, the waste burden is expected to reach 40–60 million tons by 2050. Traditional disposal methods, like mechanical and thermochemical recycling, are costly and result in low-value materials. Repurposing presents a sustainable alternative; however, matching decommissioned blades with appropriate industrial applications requires an innovative governance approach. This study leverages insights from innovation governance research and proposes a conceptual model for reusing decommissioned blades, focusing on bridging the gap between potential suppliers and users in various industries. By examining applications in construction, agriculture, and renewable energy systems, the study illustrates feasible repurposing strategies and explores the regulatory mechanisms needed to facilitate effective matching. Through expert interviews and case studies, the paper identifies barriers, such as logistical constraints and material degradation, and advocates for intermediate and third-party governance forms to support this marketization process. The findings highlight the importance of systematic matching mechanisms and regulatory frameworks in addressing the wind turbine blade disposal issue, underscoring the need for collaborative efforts in shaping sustainable solutions for end-of-life turbine materials.